Pengembangan Bahan Ajar untuk Mata Kuliah Kriya Batik - Hasnawati, Hasnawati (Indonesian Journal of Educational Studies, 2018)
This study aims to design batik learning teaching materials for students in the Fine Arts Education Study Program. This type of research is development research, which is the design of batik learning teaching materials. Data collection techniques were carried out by observation, interviews, questionnaires, and documentation. Data analysis was performed with qualitative descriptive analysis techniques. The results of this study are known that the development of teaching materials in the Textile Craft Art subject through several stages, namely: the needs analysis phase through two stages, namely the field study and literature studies, the development phase of learning strategies through the semester program plan assessment, the development of teaching materials the materials related to technical skills, and the realization of the initial teaching materials, and adapted to the Semester Program Plan (RPS) that had been developed previously. This teaching material has not yet been carried out by the expert eavaluation stage, both material experts, media experts and experiments.